Fumarate reductase drives methane emissions in the genus Oryza through differential regulation of the rhizospheric ecosystem - Jia Hu; Girma Bedada; Chuanxin Sun; Choong-Min Ryu; Anna Schnürer; Pär K. Ingvarsson; Yunkai Jin (Environment International, 2024)
The emergence of waterlogged Oryza species ∼15Mya (million years ago) supplied an anoxic warm bed for methane-producing microorganisms, and methane emissions have hence accompanied the entire evolutionary history of the genus Oryza. However, to date no study has addressed how methane emission has been altered during Oryza evolution. In this paper we used a diverse collection of wild and cultivated Oryza species to study the relation between Oryza evolution and methane emissions. Phylogenetic analyses and methane detection identified a co-evolutionary pattern between Oryza and methane emissions, mediated by the diversity of the rhizospheric ecosystems arising from different oxygen levels. Fumarate was identified as an oxygen substitute used to retain the electron transport/energy production in the anoxic rice root, and the contribution of fumarate reductase to Oryza evolution and methane emissions has also been assessed. We confirmed the between-species patterns using genetic dissection of the traits in a cross between a low and high methane-emitting species. Our findings provide novel insights on the evolutionary processes of rice paddy methane emissions: the evolution of wild rice produces different Oryza species with divergent rhizospheric ecosystem attributing to the different oxygen levels and fumarate reductase activities, methane emissions are comprehensively assessed by the rhizospheric environment of diversity Oryza species and result in a co-evolution pattern.